Is Bitcoin a safe haven for equity markets during the Covid-19 pandemic? - Lai, Eunice (2022)
Bitcoin has always been called as the digital gold based on the idea that it can hold its value during periods of market stress. However, since the introduction of Bitcoin in 2009, there has never been a global crisis as significance as the current Covid-19 to properly prove the claim. Using value at risk approach, this paper investigates whether Bitcoin exhibits a safe haven property during the period of acute market losses and made comparison with gold as the traditional safe haven assets. Results show that introducing Bitcoin into portfolio fails to provide shelter from turbulence in the equity markets. Although Bitcoin shows to reduce portfolio risk in some sub-Covid-19 periods, we cannot simply rely on Bitcoin in reducing downside risk. Gold, however, maintains its safe haven ability consistently throughout the pandemic. Bitcoin is not the digital gold.